Effect of exchange transfusion in bilirubin and calcium level in Neonatal Hyperbilirubinemia - Manishi Singh; Manika Singh; Surya Tiwari (International Journal of Medical Research and Review, 2015)
Background: Hyperbilirubinemia is very common and usually benign in the term newborn infant and late preterm infant at 35-36 completed weeks’ gestation. Critical hyperbilirubinemia is uncommon but has the potential for causing long term neurological impairment. The present study is designed to determine the effect of exchange transfusion in biochemical parameters in pre-term and full term infants.Methodology: Sixty newborns who underwent double volume exchange transfusion for different indications were studied. The infants were divided into two groups, Group A containing Full term infants and Group B containing Preterm infants. Blood samples were obtained and the following tests were performed i.e. serum bilirubin and blood calcium.Result: A significant decrease in serum bilirubin values was observed in both the groups after exchange transfusion. Also a significant elevation of blood calcium level was found in both the groups of infant studied.Conclusion: Careful monitoring of the risk factors involved a systematic approach to the detection and follow - up of jaundice with the appropriate laboratory investigations, along with judicious exchange transfusion when indicated, are all essential to avoid these complications.